INTERNATIONAL JOURNAL OF EDUCATIONAL MANAGEMENT (IJEM) 2021 - Fasasi , Y. A.; Oduwaiye , hoda 0. (International Journal of Educational Management, 2025)
I am highly privileged to write a foreword on this special edition of International Journal of Educational Management (IJEM), a publication of the Department of Educational Management, University of Ilorin. This edition is published in honour of Professor David Olufemi Durosaro, a Professor of E ducational Management, to mark his 70 birthday and retirement from active service. T he theme of this edition is Educational cost Analysis for Decision making. It emanate from an area of specialization and research interest of professor David Olufemi Durosaro. While the theme and the Sub-themes may not totally capture his areas of research, they provide a fair representation of his contributions to knowledge and scholarship in the area of Education Financing. Scholars of Education financial resource Management have contributed their well researched empirical and theoretical papers in simple terms which can be easily understood by practicing and prospective management of educational i n stitution, scholars researchers, policy-maker and all stakeholder moreover, techniques for rational decision-making and financial preparation for the future a s emphasized in different parts of this publication will provide additional b enefits to all readers.